2020
DOI: 10.1103/physrevlett.124.023603
|View full text |Cite
|
Sign up to set email alerts
|

Topologically Protected Quantum Coherence in a Superatom

Abstract: Exploring the properties and applications of topological quantum states is essential to better understand topological matter. Here, we theoretically study a quasi-one-dimensional topological atom array. In the low-energy regime, the atom array is equivalent to a topological superatom. Driving the superatom in a cavity, we study the interaction between light and topological quantum states. We find that the edge states exhibit topology-protected quantum coherence, which can be characterized from the photon trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 98 publications
0
25
0
Order By: Relevance
“…Blended orbitals clearly offer novel possibilities not yet fully explored. Moreover, such blended nonbonding orbitals seem to be what is described [ 36–38 ] in the physics literature as “topological insulators,” which nevertheless conduct along the boundary, and to be, [ 91–97 ] a “topologically protected” feature (see also, refs. [62,65]).…”
Section: Edge States On Translationally Symmetric Graphene Boundariesmentioning
confidence: 99%
“…Blended orbitals clearly offer novel possibilities not yet fully explored. Moreover, such blended nonbonding orbitals seem to be what is described [ 36–38 ] in the physics literature as “topological insulators,” which nevertheless conduct along the boundary, and to be, [ 91–97 ] a “topologically protected” feature (see also, refs. [62,65]).…”
Section: Edge States On Translationally Symmetric Graphene Boundariesmentioning
confidence: 99%
“…Depending on the specific geometry of the system, the scattering coefficients can be readily obtained by taking the mean value of the field operators in Eqs. ( 17)- (18) for hanger-type resonators, or in Eqs. ( 37)- (38) for necklace-or bridge-type resonators.…”
Section: The Bridge-type λ/2 Resonatorsmentioning
confidence: 99%
“…Understanding the scattering coefficients of superconducting microwave resonators is crucial to the study of superconducting quantum circuits [1]. Owing to the high design flexibility and the strong interactions, a variety of novel photon transport properties emerge when coupling a microwave resonator to other circuit components [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For example, it is shown that a dissipative atom can completely reflect the photons propagating along a 1D waveguide with no loss [2][3][4], although the physical size of the atom is much smaller than the wavelength of the propagating microwave field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many-body localization [37,38], Mott insulator of photons [40] and correlated quantum walk [41] are observed in 1D qubit arrays. With these experimental achievements, superconducting qubit systems are hopeful to simulate topological matter [42][43][44][45][46].…”
mentioning
confidence: 99%
“…Vacuum Rabi splitting for resonant coupling between the cavity and edge modes-. To show how to manipulate the qubit array by the quantized field in the cavity, we rewrite the states |A i and |B i of qubits A and B in the ith unit cell via eigenstates |Ψ j in the singleexcitation subspace of the qubit array [46], i.e.,…”
mentioning
confidence: 99%